2003
DOI: 10.3127/ajis.v10i2.159
|View full text |Cite
|
Sign up to set email alerts
|

Doing Ethics: A Universal Technique in an Accessibility Context

Abstract: Thinking ethically is difficult without a background in moral philosophy. Asking people to embrace ethics without offering practical explanation of the efficacy of so doing, is a thankless task. A technique that people can follow easily, that helps them value ethical behaviour is needed. Illustrations of such a procedure show how professional scenarios are used in the domain of web accessibility. Scenario design and extensions to the technique are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Miah et al (2019) adopted a thematic analysis approach for analysing and classifying the existing literature to summarise new insights that may have future research value. It extends previous health informatics publications in this journal (Burmeister, Islam, Dayhew, & Crichton, 2015;Carlson, Farrelly, Frazer, & Borthwick, 2015;Poulsen, 2018;Simpson, Nevile, & Burmeister, 2003) and other IS journals . Chiefly, the study identified ten research themes regarding existing health informatics by succinctly encapsulating the emerging aspects of this multidisciplinary IS subset.…”
supporting
confidence: 76%
“…Miah et al (2019) adopted a thematic analysis approach for analysing and classifying the existing literature to summarise new insights that may have future research value. It extends previous health informatics publications in this journal (Burmeister, Islam, Dayhew, & Crichton, 2015;Carlson, Farrelly, Frazer, & Borthwick, 2015;Poulsen, 2018;Simpson, Nevile, & Burmeister, 2003) and other IS journals . Chiefly, the study identified ten research themes regarding existing health informatics by succinctly encapsulating the emerging aspects of this multidisciplinary IS subset.…”
supporting
confidence: 76%
“…Through this process, learning then becomes an experience and provides students with the knowledge to perform effectively, as recently demonstrated in a similar course at another university Sixsmith 2014a and2014b). These studies build on a tradition of student engagement in Information and Communications Technology (ICT) (Al-Saggaf & Burmeister, 2012;Burmeister, 1995;Simpson, Nevile, & Burmeister, 2003), which demonstrate that it is this active learning experience that has a profound influence on learning outcomes.…”
Section: Reviewmentioning
confidence: 99%
“…And their perceptions of that moral intensity will be influenced by the type of moral education they had. Although there have been many attempts to improve ICT ethics education (Al-Saggaf & Burmeister, 2012;Fleischmann, 2010;Simpson, Nevile, & Burmeister, 2003), it appears that it has only had limited effect. A study of the perceptions of recent graduates, who had been working for at least 18 months, revealed that despite their course having a dedicated final year ethics subject, nothing they had studied had prepared them for the types of ethical dilemmas that they faced in their employment (Burmeister & Sharma, 2005).…”
Section: Qualifications and Ethics Educationmentioning
confidence: 99%